A potential significance of circ_0024169 down regulation in angiosarcoma tissue - Nakashima, Satoko (Intractable Rare Dis Res, 2019)
Circular RNAs (circRNAs) are recently characterized non-coding RNAs that have a closed continuous loop. CircRNAs might play important roles in the oncogenesis of several cancers. However, little is known about association between circRNAs and skin tumors. In this study, we tried to demonstrate the expression change of circ_0024169 in angiosarcoma, and to elucidate correlations between circ_0024169 expression in angiosarcoma tissues and clinical manifestation. RNA expression was evaluated by quantitative real-time PCR with TaqMan systems for circ_0024169 and linear isoform CUL5. Both relative circRNA levels (corrected for EEF1A1 levels) and circRNA levels/linear RNA expression ratio were evaluated. We found that both relative circ_0024169 levels and circ_0024169/CUL5 ratio was decreased in normal human dermal microvascular endothelial cells (HDMEC) and angiosarcoma cell line in vitro, compared to squamous cell carcinoma line. circ_0024169/ CUL5 ratio was significantly reduced in angiosarcoma and pyogenic granuloma than other tumors in vivo, which were more evident than decreased relative circ_0024169 levels. On the other hand, relative circ_0024169 levels showed mild inverse correlation with the follow-up periods (duration between the first hospital visit and the last hospital visit/the date of death) of angiosarcoma patients. Taken together, circ_0024169/CUL5 ratio are likely to be useful as a diagnostic biomarker for vascular tumors, whereas circ_0024169 levels may have more potential as a prognostic marker of angiosarcoma. The future studies of the function of circRNAs may lead to the clarification of detailed mechanism of oncogenesis of angiosarcoma.